Genangan Banjir Sungai Gajahwong Yang Berdampak Terhadap Permukiman Bantaran Sungai di Kelurahan Pandeyan - Muchamad Arif Budiyanto; Muhamad Arifin; Muhammad Ryan Iskandar; Muhammad Arif Hidayatullah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Flood events in Gajah Wong River have caused significant damages such as collapsed riverbanks, damaged neighborhood roads, and forced evacuations. The objective of this study is to visualize the areas along the Gajah Wong River that are affected by flooding during rainfall events, in order to determine the extent of inundated areas under specific return period discharges. This research aims to produce a flood inundation prediction map for the Gajah Wong River as a basis for flood mitigation efforts. The study uses primary data obtained through GNSS surveys, aerial photography, and river depth sampling. Secondary data used include return period discharges for Q2, Q10, and Q25. To calculate the inundated area, the researchers applied photogrammetry methods to generate orthophoto and DEM data, which were then simulated using HEC-RAS software to determine the flood inundation extent. The results of the study show that the flood-affected areas along the Gajah Wong River have inundation extents of 3.208 hectares for Q2, 3.942 hectares for Q10, and 4.601 hectares for Q25.